SZLACHECTWO NIE ZOBOWIĄZUJE ZMIANY WE WZORACH KONSUMPCJI KULTUROWEJ - Strzyczkowski, Konstanty (Wydział Prawa i Administracji UAM, 2009)
The paper is an attempt to examine the concepts that associate cultural tastes with different social backgrounds. In Pierre Bourdieu’s theory, preferences concerning cultural consumption are coordinated by a habitus that is inherent to each social class. This, in turn, leads to the homogeneity of cultural choices, which is a primary condition for a distinctive lifestyle. In consequence, different lifestyles participate in a hierarchy that resembles the social hierarchy. Hence the conclusion that the most legitimate cultural choices (made within a highbrow culture) remain in the competence of privileged groups, possessing sufficient cultural and economic capital to undertake them. Recent research into the culture consumption include the revision of such a view. Richard Peterson and others point out to the phenomenon of cultural omnivorousness. As he discovers, people of higher social status, contrary to the elite-mass model, do not show aversion to activities associated with popular culture. The main aim of this paper is to present the results of the latest research concerning this new trend in cultural consumption, to identify its causes, and to propose its possible interpretations.
NOBILITY DOES NOT OBLIGATE: CHANGES IN THE CULTURAL CONSUMPTION MODELS